Nano- and micro- mechanics of polymer blends and composites - Fakirov, Stoyko; Karger-Kocsis J. (Jszsef) (Hanser, 2009)
The aim of this book is to give a state-of-art overview on aspects of micro- and nanomechanics of polymers, polymeric blends and composites